(untitled) (Tempo e Argumento, 2022)
At the end of the 20th century, there was an increase in the perception, in the international community, of the movement of migrant workers, of flows of people in search of a better life and who were faced with increasingly restrictive migratory policies. In this scenario, there has been a growth in children who migrate alone or unaccompanied by their parents, held back at the borders. Thus, although, in demographic terms, we cannot speak of an expansion of migrant flows, as international rates are around 3%, the media narratives about these flows build a discourse of “invasion”, of threat, spreading moral panic in relation to these flows. to immigrants, contributing to their being treated with prejudice and discrimination. Thus, immigrants and refugees, including unaccompanied children, constitute a “new” category of undesirables that emerges at the beginning of this century. The objective of this article is to understand, from the production that crosses perspectives of Transnational History, Anthropology of Mobilities and Sociology, the fear of the “other”, which translates into increasingly harsh and restrictive surveillance systems, which led to the increased incarceration of unaccompanied children and adolescents at borders. The article analyzes children separated from their families on the border between Mexico and the United States, in shelters and transit centers, where they are placed in a situation similar to that of prisons, as they are incarcerated. The sources are a bibliographic survey on unaccompanied children, articles found in the press, IOM and UN data on the incarceration of children, through which we seek to understand the contexts in host societies that produce hierarchies between desirable and undesirable migrants.